2016
DOI: 10.1007/s12041-016-0716-0
|View full text |Cite
|
Sign up to set email alerts
|

Three novel and two known androgen receptor gene mutations associated with androgen insensitivity syndrome in sex-reversed XY female patients

Abstract: Molecular characterization of 23 cytogenetically confirmed XY females was attempted by screening coding regions of SRY and androgen receptor (AR) genes. Five of the index cases showed sequence variations in various exons of the AR gene: a deletion (n.1911delG) and substitutions n.1761G>A and n.1317C>T in exon 1; n.3510C>T transition in exon 6 and deletion mutation (n.3672delT) in exon 7. Four mutations identified here lead to the formation of truncated receptor protein, involving a substantial loss of AR funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Pathogenic variants in the LBD were present in 13/19 (68.4%) followed by 3/19 (15.8%) in the NTD and DBD each. Similar findings have been noted previously [Gottlieb et al, 2012;Saranya et al, 2016;Yuan et al, 2018], suggesting that the LBD is more susceptible to being a hotspot region for pathogenic variants in patients with AIS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pathogenic variants in the LBD were present in 13/19 (68.4%) followed by 3/19 (15.8%) in the NTD and DBD each. Similar findings have been noted previously [Gottlieb et al, 2012;Saranya et al, 2016;Yuan et al, 2018], suggesting that the LBD is more susceptible to being a hotspot region for pathogenic variants in patients with AIS.…”
Section: Discussionsupporting
confidence: 89%
“…More than 1,100 different pathogenic variants including deletions, duplications, insertions, and point variants have been documented in the AR gene (www.androgendb.mcgill.ca), with the majority being missense pathogenic variants. There are very few studies from India on clinical, biochemical, and molecular aspects of AIS, the majority being case reports [Abilash et al, 2016;Saranya et al, 2016;Akella, 2017], and no hotspot pathogenic variant has been identified [Nagaraja et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…AIS is the most common cause of the 46,XY disorder in sex development. Point mutations within the AR LBD are frequently described in this disease . The AR LBD possesses a three-layer sandwich fold architecture (Figure S1A).…”
Section: Introductionmentioning
confidence: 99%